การศึกษาเปรียบเทียบวิธีการตรวจยาบ้าในปัสสาวะโดยวิธีต่างๆ - Noyprasert, Pakron; Joucharoen, Chanida (วารสารแพทย์เขต 4-5, 2018)
The pills of methamphetamine were easy to take and addict. The important to epidemic control were the detection in urine. There are several methods for detection of methamphetamine in urine. Each method has different sensitivity and precision, comparative study were made. Student, patient and criminal urine 373 samples were tested in 4 methods e.g. GC, TLC, immunoassay and Color test. The positive result were 181, 187, 177 and 320 samples respectively (48.52%, 50.13%, 47.15% and 85.79%). When compare with GC method (Gold standard method) TLC, Immunoassay and Color test were 1.61%, 1.07%, and 37.27% difference. Then, the red-violet result 111 samples and the other violet result 209 samples of color test were confirmed, they had positive 87 and 92 samples (78.37% and 44.02%). The green result 53 samples of color test were confirmed and positive 51 samples (96.02%). For epidemic control, the urine methamphetamine tests using color test and immunoassay, but for criminal purpose TLC and GC method should be used.